Riemann Integral on Fractal Structures - José Fulgencio Gálvez-Rodríguez; Cristina Martín-Aguado; Miguel Ángel Sánchez-Granero (Mathematics, 2024)
In this work we start developing a Riemann-type integration theory on spaces which are equipped with a fractal structure. These topological structures have a recursive nature, which allows us to guarantee a good approximation to the true value of a certain integral with respect to some measure defined on the Borel <semantics>σ</semantics>-algebra of the space. We give the notion of Darboux sums and lower and upper Riemann integrals of a bounded function when given a measure and a fractal structure. Furthermore, we give the notion of a Riemann-integrable function in this context and prove that each <semantics>μ</semantics>-measurable function is Riemann-integrable with respect to <semantics>μ</semantics>. Moreover, if <semantics>μ</semantics> is the Lebesgue measure, then the Lebesgue integral on a bounded set of <semantics>Rn</semantics> meets the Riemann integral with respect to the Lebesgue measure in the context of measures and fractal structures. Finally, we give some examples showing that we can calculate improper integrals and integrals on fractal sets.